The implementation of virtual home laboratories to improve students psychomotor abilities - Hesti Noviyanti; Yusro Al Hakim; Eko Setyadi Kurniawan; R. Wakhid Akhdinirwanto (Jurnal Pijar Mipa, 2022)
Psychomotor relates to learning outcomes that are achieved through skills as a result of knowledge competence. Learning that still uses the demonstration method and has not optimized learning activities in the laboratory. This study aims to determine how implementing a virtual home learning laboratory improves students' psychomotor abilities. This study uses a quasi-experimental method with a nonequivalent control group design. The sample used in this study was 46 respondents from the Mathematics and Natural Sciences Department at Senior High School 8 Purworejo, Indonesia. The research sample consisted of two classes: the control and experimental classes. The instruments used in this study were learning implementation sheets, psychomotor observation sheets, student response questionnaires, and students' psychomotor ability test instruments. The data analysis technique in this research is quantitative, and the t-test. The analysis of test data using the N-gain test obtained 0.75 for the experimental class with high category and 0.29 for the control class with low category results. The statistical analysis results of the independent sample t-test show that laboratory implementation affects the psychomotor abilities of students.